Storytelling and improving the speaking skill among ninth-year students at a public school in Loja city. School year 2021-2022. Narración de historias y el mejoramiento de la habilidad de hablar con los estudiantes de noveno año de un colegio público de la ciudad de Loja. Año electivo 2021-2022. - Ramón Maldonado, Nathaly Antonela (2022)
The main goal of this research was to improve students’ speaking skill through storytelling strategy among ninth-year students at a public school in the Loja city 2022-2022. The participants were twenty-six students in 9th year. The researcher used a mixed methodology to obtain the data for this study. The quantitative data was gathered through a pretest and posttest, meanwhile, the qualitative data was gotten from a semi-structured interview. data collected was analyzed by using statistical formulas of the Wilcoxon test presented in tables and graphs and with a thematic analysis presented in a narrative form. The results demonstrated a significant difference before and after the implementation of storytelling to develop the students’ speaking skill. Moreover, the results showed that students achieved a satisfactory improvement in the five elements of speaking skill, which were: vocabulary, grammar, fluency, pronunciation, and comprehension. In addition, through the storytelling strategy, students showed a great interest in actively participating in speaking activities. Key words: fluency, grammar, pronunciation, speaking skill, storytelling, vocabulary.